Near-Miss Diagnoses of Solitary Bladder Tumors Highlight the Importance of Immunohistochemical Staining - Van Schloegel; Syed M. Alam; Katie Dennis; Jeffrey Holzbeierlein; John A. Taylor III (Case Reports in Urology)
We report three cases of prostate adenocarcinoma appearing as bladder masses and misdiagnosed as muscle-invasive bladder cancer (MIBC). Patients were referred for consideration for radical cystectomy after initial pathological diagnosis suggested poorly differentiated bladder cancer. Pathological review of tissue samples and subsequent immunohistochemical (IHC) staining confirmed advanced prostatic adenocarcinoma. Systemic therapy for prostate cancer was then initiated. These cases highlight the importance of patient history, physical exam, and IHC staining in consideration of a bladder mass, as these patients may have been subject to undue morbidity and surgical intervention without accurate pathologic diagnosis.